Pre-service English teachers’ learning traits - Óscar Manuel Narváez Trejo; Cliserio Antonio Cruz Martínez; Carolina Reyes Galindo (Sinéctica)
The present study aimed to characterize a comprehensive learning profile of pre-service teachers at an English teacher education programme of a public university in Southeast Mexico. The learning attributes comprise their English entry level, learning strategies and styles, learning approaches, and learning preferences. The research design was non-experimental, descriptive transectional, with a single data collection procedure during the August 2023 term. Four learning scales and two placement tests were used to identify the predominant learning traits of the cohort studied. The results show a preference to use cognitive learning strategies more than any other type. In terms of learning styles, the findings show that most participants are primarily aural, but some students are bi- and even tri-oriented. In terms of their learning preferences, most students identified as analytical. Regarding learning approaches, most students typically employ a deep approach, which could be quite inadequate because they depend more on surface strategies.